Renormalized energy of ground and first excited state of Fröhlich polaron in the range of weak coupling - Tkach, M.V.; Seti, Ju.O.; Voitsekhivska, O.M.; Pytiuk, O.Yu. (Condensed Matter Physics, 2015)
The partial summing of infinite range of diagrams for the two-phonon mass operator of polaron described by Frohlich Hamiltonian is performed using the Feynman-Pines diagram technique. The renormalized spectral parameters of ground and first excited (phonon repeat) polaron state are accurately calculated for the weak electron-phonon coupling at T=0 K. It is shown that the stronger electron-phonon interaction shifts the energy of both states into low-energy region of the spectra. The ground state stays stationary and the excited one - decays at bigger coupling constant.